Voice Management In The Mawlid By Mirza Safvet-Beg Bašagić - Bulić, Halid (Slavica Lodziensia, 2017)
Mawlid is a poetic literary work about the birth and life of the Muhammad, the Messenger of God. Mawlid by Mirza Safvet-beg Bašagić is one of the most signifi cant mawlids written in the Bosnian language. The text of the Mawlid is analyzed from the perspective of literary pragmatics. The paper takes into consideration the relationship between the author and narrator in the text and voice management in the Bašagić’s Mawlid.